Investigation of wrist release during the golf swing by using a golf swing robot - Hoshino, Y.; Kobayashi, Y.; Suzuki, S. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
In this study, skill of the wrist release during golf swing is investigated by using a golf swing robot. A torque plan of the shoulder joint of the robot is assumed as a two-steps modulation torque that is a simplification of the acceleration torque induced by the weight shift, rotation of torso and the shoulder of a golfer. Relationship between the torque plan and the skill of the wrist release, such as natural release and late hitting, is investigated by using the golf swing robot.